EFFECTS OF ADDITIONAL CORE MUSCLE TRAINING ON CYCLING PERFORMANCE IN YOUTH MALE TIME TRIAL CYCLISTS - Nualpech, Wirungrong; Chuensiri, Napasakorn; Suksom, Daroonwan (Journal of Sports Science and Health, 2019)
Purpose To determine the effects of additional core muscle training on cycling performance in youth male time trial cyclists Methods Youth male time trial cyclists, mean aged 16±2 years, were recruited. The purposive sampling by ranking core muscle strength was used to divide the participants into two groups: the cycling training group (CT; n=13) and the cycling combined with core muscle training group (CT+CMT; n=12). Both groups performed cycling training program at the intensity of 65-80 %HRmax twice a week and 80-90 %HRmax for 4 days/ week. The additional core muscle training program consisted of core muscle training using Swiss ball and weight machine at the intensity of 75%of 1 Repetiton Maximum (RM) for 2 days/week. The variables including general physiological, cycling performance; 20 km time trial, cycling balance skill and time to fatigue as well as core muscle strength were determined before and after 8-week of intervention period. The 2x2 (groups x times) ANOVA with repeated measures followed by LSD multiple comparisons were used to determine significant differences among all variables. Results After 8 weeks of training, maximal oxygen consumption increased in both cycling training and cycling combined with core muscle training groups (p< .05). The CT+CMT group had significantly decreased time trial 20km. duration (all p< .05). Moreover, the CT+CMT group had significantly increased time to fatigue, cycling balance skill and core muscle strength (p< .05). The CT+CMT group had significantly higher peak torque of core muscle in trunk extension and flexion positions and lower core muscle fatigue in trunk extension positions than the CT group (p< .05). Conclusion The cycling combined with core muscle training can improve cycling performance such as cycling balance skill, time to fatigue and time trial 20 km. duration while the cycling training only did not improve those cycling performances.